Mesenchymal Stromal Cells for Enhancing Hematopoietic Engraftment and Treatment of Graft-Versus-Host Disease, Hemorrhages and Acute Respiratory Distress Syndrome - Ringdén, Olle; Moll, Guido; Gustafsson, Britt; Sadeghi, Behnam (Frontiers in Immunology, 2022)
Mesenchymal stromal cells (MSCs) possess profound immunomodulatory and regenerative properties that are of medical use in numerous clinical indications with unmet medical need. Common sources of MSCs include among others, bone marrow (BM), fat, umbilical cord, and placenta-derived decidua stromal cells (DSCs). We here summarize our more than 20-years of scientific experience in the clinical use of MSCs and DSCs in different clinical settings. BM-MSCs were first explored to enhance the engraftment of autographs in hematopoietic cell transplantation (HCT) and osteogenesis imperfecta around 30 years ago. In 2004, our group reported the first anti-inflammatory use of BM-MSCs in a child with grade IV acute graft-versus-host disease (GvHD). Subsequent studies have shown that MSCs appear to be more effective in acute than chronic GvHD. Today BM-MSC-therapy is registered for acute GvHD in Japan and for GvHD in children in Canada and New Zeeland. MSCs first home to the lung following intravenous injection and exert strong local and systemic immunomodulatory effects on the host immune system. Thus, they were studied for ameliorating the cytokine storm in acute respiratory distress syndrome (ARDS). Both, MSCs and DSCs were used to treat SARS-CoV-2 coronavirus-induced disease 2019 (COVID-19)-induced ARDS. In addition, they were also used for other novel indications, such as pneumomediastinum, colon perforation, and radiculomyelopathy. MSC and DSCs trigger coagulation and were thus explored to stop hemorrhages. DSCs appear to be more effective for acute GvHD, ARDS, and hemorrhages, but randomized studies are needed to prove superiority. Stromal cell infusion is safe, well tolerated, and only gives rise to a slight fever in a limited number of patients, but no major side effects have been reported in multiple safety studies and metaanalysis. In this review we summarize current evidence from in vitro studies, animal models, and importantly our clinical experience, to support stromal cell therapy in multiple clinical indications. This encloses MSC's effects on the immune system, coagulation, and their safety and efficacy, which are discussed in relation to prominent clinical trials within the field.